ENDOCRINE EFFECT OF GHRELIN ON HISTOLOGICAL, HORMONAL AND MORPHOMETRIC PARAMETERS OF THE PITUITARY GLAND AND THE POSSIBILITY OF ITS CLINICAL APPLICATION - Čukuranović Kokoris, Jovana (Journal of Medical Biochemistry, 2025)
Background: Ghrelin, a brain-intestinal hormone, is a growth hormone (GH) secretagogue. As it regulates appetite and is most secreted before meals, it is often described as a "hunger hormone". It consists of 28 amino acids. Given the connection between nutritional status and energy metabolism, it suggests that disorders in these areas can lead to anorexia, especially during aging. The aim of this review article is to demonstrate the influence of ghrelin on the histological, hormonal, and stereological characteristics of pituitary cells, as well as its potential clinical applications. Methods: To write this review, we performed an electronic literature search through Google Scholar and PubMed databases with the terms ghrelin, structure, pituitary cells, metabolism, and aging, with reference to the authors and co-authors of published works related to this topic, as well as the option "related articles", which were related to the content of this publication. Results: The topic of this review article relates to the structure, morphometric and hormonal characteristics of adrenocorticotropic (ACTH), somatotropic (GH), and gonadotropic (FSH and LH) pituitary cells in control and ghrelin-treated rats. Conclusion: This review showed that central administration of nanomolar doses of ghrelin to rats has a modulatory role on the immunohistomorphometric and hormonal characteristics of pituitary hormone-producing cells. The changes are particularly significant in the volume of corticotropes, somatotropes and luteinizing hormone (LH) producing cells, their volume density, and the levels of hormones they secrete compared to the control group.